The hallmarks of ovarian cancer: Focus on angiogenesis and micro-environment and new models for their characterisation. (August 2020) - Heredia-Soto, V.; López-Guerrero, J.A.; Redondo, A.; Mendiola, M.
Abstract: Cancers develop by sustained growth, migration and invasion properties of tumour cells, supported by complex interactions with stromal cells within the tumour micro-environment. This review is focused on the latest discoveries regarding the highlighted role of angiogenesis and tumour micro-environment in ovarian cancer. This cancer milieu encompasses non-cancerous cells present in the tumour or nearby, including vessel-forming cells, fibroblasts and immune cells amongst others that work in a cooperative way with cancer cells, impacting tumour behaviour. Angiogenesis, migration and invasion, and more recently immune evasion, are cancer hallmarks clearly dependent on these supporting cells. Moreover, these stromal cells are more genetically stable than tumour cells and thus represent an attractive therapeutic target. A better understanding of the stromal cells function, and their complex interplay with cancer cells, will open additional areas to target, as the tumour–host interface. Highlights: Cancer micro-environment is composed of cells that work cooperatively with tumour cells. These supporting cells include vessel-forming cells, fibroblasts and immune cells, amongst others. Angiogenesis, migration, invasion and immune evasion clearly impact on tumour behaviour. Currently pre-clinical models allow the study of tumour and stromal cells interplay. The better knowledge of stromal cells function will open additional areas to target tumours.